2019
DOI: 10.1056/nejmoa1805376
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Nipah Virus — 14 Years of Investigations in Bangladesh

Abstract: BACKGROUND Nipah virus is a highly virulent zoonotic pathogen that can be transmitted between humans. Understanding the dynamics of person-to-person transmission is key to designing effective interventions. METHODS We used data from all Nipah virus cases identified during outbreak investigations in Bangladesh from April 2001 through April 2014 to investigate case-patient characteristics associated with onward transmission and factors associated with the risk of infection among patient contacts. RESULTS Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
174
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(188 citation statements)
references
References 32 publications
0
174
0
Order By: Relevance
“…Fortunately, as with the MERS-CoV, there is relatively inefficient NiV person-to-person transmission; however, 90% of those infected progress to acute encephalitis with respiratory complications, and 30% of those who survive experience neurological sequelae. A contact survey that was conducted showed that asymptomatic infections have likely been rare in Bangladesh (Nikolay et al, 2019).…”
Section: Development Of Medical Countermeasures Against Nipah Virus: mentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, as with the MERS-CoV, there is relatively inefficient NiV person-to-person transmission; however, 90% of those infected progress to acute encephalitis with respiratory complications, and 30% of those who survive experience neurological sequelae. A contact survey that was conducted showed that asymptomatic infections have likely been rare in Bangladesh (Nikolay et al, 2019).…”
Section: Development Of Medical Countermeasures Against Nipah Virus: mentioning
confidence: 99%
“…Models combining healthcare utilization surveys and active NiV case finding efforts at three Bangladesh hospitals suggest that only half of the actual cases are being detected (Hegde et al, 2019). In terms of transmission, males experiencing breathing difficulty were found to be the most efficient at person-to-person transmission (Nikolay et al, 2019). As reviewed by Emily Gurley, caregivers are at greatest risk of infection.…”
Section: Development Of Medical Countermeasures Against Nipah Virus: mentioning
confidence: 99%
“…Drinking date palm sap contaminated with urine or saliva of NiV‐infected bats has been identified as a major route of zoonotic transmission of NiV (Chakraborty et al, ; Luby & Gurley, ). However, human‐to‐human NiV transmissions represent 33% of known Nipah virus human cases from Bangladesh between 2001 and 2014 (Nikolay et al, ). This observation, coupled with high mortality rates and the lack of effective therapies or vaccines (Vigant & Lee, ), marks NiV as a significant public health threat in the region with potential for pandemic spread (Luby, ).…”
Section: Introductionmentioning
confidence: 99%
“…2f). Indeed, the facultative 17 heterochromatin marker H3K27me3 in bat RSCs was distributed within several large foci, rather than 18 being concentrated mainly at the inactivated X chromosome as in PCs. Previously, such numerous 19 prominent H3K27me3 foci were observed in both naïve mouse PSCs33 and in pluripotent and 20 reprogrammed avian cells 31,34 .…”
mentioning
confidence: 99%
“…Isolation of new viral strains is an important step and is (generally) 15 attempted in established immortalized cell lines such as IFN-I-deficient simian Vero cells. 16 Propagation of viruses in cell lines other than those of the natural host may lead to selection of virus 17 sub-populations that replicate more efficiently in the chosen cell type, leading to accumulation of 18 adaptive mutations that may prevent adequate assessment of host-pathogen interactions 23 . Therefore, 19 further advancement in the field requires establishment of new bat cell models; indeed, development 20 of novel Pteropus cell lines is particularly important for the field of Henipavirus infection research.…”
mentioning
confidence: 99%